ANALYSIS OF FACTORS AFFECTING THE PROFITABILITY OF ISLAMIC BANKS WITH ISLAMIC SOCIAL REPORTING AS A MODERATION FACTOR - Haryono Susilo; Rani Rahman; Widyahayu (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study aims to investigate the impact of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on profitability, as measured by Return on Assets (ROA) and Return on Equity (ROE), with moderated Islamic Social Reporting (ISR) in Sharia commercial banks in Indonesia from 2018 to 2024. The Data used in this study are from 2018 to 2024, which aims to analyze the profitability of Islamic commercial banks. Through using secondary data sourced from the Annual Report of Bank Umum Syariah, which has been published. Data analysis in this study was conducted using multiple linear regression analysis using SPSS version 25. The results of this study showed that NPF harms profitability, FDR does not affect profitability, in addition, ISR does not moderate the negative influence of NPF on profitability when measured by ROA and ROE, ISR does not moderate the outcome of FDR on profitability when measured by ROA, but then again moderates when measured by ROE.